VERBA AKTIVITAS KAKI DALAM BAHASA MINANGKABAU UMUM - Suryani, Irma; Agustina, Agustina; Ngusman, Ngusman (Universitas Negeri Padang, 2018)
This study aims to (a) describe the verb form of foot activity in Minangkabau language, (b) describe the process of derivative verbs of foot activity in Minangkabau language, (c) describe the type of verb of foot activity in Minangkabau language. This research is qualitative research and using descriptive analysis method. Methods and techniques of data collection using method refer with noted and record techniques, then used the skill methold wilh advanced skill technique. Result of this study, First, the verb form of foot activity in Minangkabau language in Padang City consists of two forms namely the original form, and the derived form. The derived verbs are grouped again into (a) mandatory affixed base verbs, (b) basic affix verbs grouped arbitrarily, (c) bound affixed verbs, (d) recurring verbs, and (e) compound verbs. Second, the process of derivative verbs of foot activity in Minangkabau language in Padang City consists of four (1) transpositions, (2) affixation, (3) reduplication, and (4) compounding. Third, the type of verb foot activity in the Minangkabau language in Padang City is divided basid on the point of view (1) the number of nouning nouns, (2) the relation of verb with the accompanying are grouped into two, namely intransitive verbs, and transitive verbs. The types of transitive verbs are grouped into three, namely (1) monotransitive verbs, (2) bitransitive verbs, and (3) ditransitive verbs. Based on the viewpoint of the relationship of verbs with nouns, grouped into four, namely (1) active verbs, (2) passive verbs, (3) anti-verbs, and (4) anti-passive verbs.Based on the viewpoint of the number of nouns that accompany. Based on the viewpoint of the interaction between the auxiliary nouns are divided into two, namely (1)reciprocal verbs and (2) non-resolved verbs.Keywords: verb, foot activity, Minangkabau language